The Relationship Between Pregnant Women's Compliance in Consuming Iron Tablets and the Occurrence of Anemia in Pregnant Women at the Suluun Community Health Center - Aprymanti Pabimbin; Raden Maria Veronika Widiatrilupi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Anemia in pregnancy remains a major public health concern, particularly in developing countries where prevalence reaches 38%. Iron deficiency is the leading cause, contributing to adverse maternal and fetal outcomes such as preterm delivery, low birth weight, and maternal mortality. Compliance with iron supplementation is critical, yet data from North Sulawesi indicate that only 60% of pregnant women adhere to recommended intake. This study aimed to analyze the relationship between compliance with Fe tablet consumption and anemia incidence among pregnant women at the Suluun Community Health Center, South Minahasa. Using a cross-sectional design, 100 respondents were selected via purposive sampling based on Slovin’s formula. Data collection involved questionnaires assessing compliance and demographics, alongside hemoglobin measurements to determine anemia status. Statistical analysis employed Chi-Square and logistic regression tests. Results showed that 56.7% of respondents were compliant, while 43.3% were non-compliant. A significant relationship was found between compliance and anemia incidence (p=0.004), with 76.9% of non-compliant women experiencing anemia compared to 23.5% of compliant women. These findings highlight the importance of education, family support, and healthcare access in improving adherence to iron supplementation. Strengthening health programs targeting these factors is essential to reduce anemia prevalence among pregnant women.